An investigation into the nature and extent of substance abuse and preventable diseases in Nongoma, KwaZulu Natal : implications for social work - Lombard, Antoinette (University of Pretoria, 2013)
Thesis (DPhil (Social Work))--University of Pretoria, 2003.